Evaluation of a socially oriented intermediary organisation that supports low-to-middle-income communities in developing energy communities in South Africa and Colombia - Cárdenas, Juan Pablo (Department of Chemical Engineering, 2025)
Energy communities are groups of citizens that actively participate in the electricity sector, usually with community-owned renewable energy generation. These models have been widely studied and implemented in developed economies. Experts conclude that they have the potential to promote just energy transitions by democratising energy production and enabling communities to benefit. However, these models have fewer studies and implementations in developing countries. In these contexts, deploying energy communities as a vehicle of energy justice will require understanding the barriers that low-to-middle-income communities face to develop them. More importantly, it becomes necessary to define the role of intermediary organisations that will provide support and channel resources to implement energy communities. This work proposes the role that intermediary organisations should play in supporting the development of energy communities. The conceptual framework is based on available literature on energy communities. Academic papers and practical guidelines were used to synthesise the key dimensions, steps, and challenges that energy communities face. Furthermore, literature on intermediaries in transitions was used to inform the evaluation of the potential organisation that supports energy communities. The barriers to developing energy communities were identified by analysing three case real studies of energy communities in South Africa and Colombia and conducting 20 semi-structured interviews with experts in all dimensions of energy community models based in South Africa, Europe, Colombia, and Ecuador. This work concludes that intermediary organisations in these contexts must provide multi-faceted support across social, legal, technical, and financial dimensions to support communities. Furthermore, given the identified barriers in both countries, the proposed intermediary organisation could act in Colombia and South Africa. Finally, the social business model canvas evaluating the characteristics of this type of organisation is presented. The organisation's primary goal is to provide professional guidance to communities in developing shared energy solutions while ensuring efficient and transparent operations.